Observational Study Using Ultrasound to Assess Midline Labor Epidural Analgesia Placement and Analgesic Efficacy. (23rd December 2017) - Weiniger, Carolyn F.; Cobb, Benjamin; Wang, Rachel R.; Carvalho, Brendan
Abstract : Objectives: Labor epidural analgesia failure may relate to nonmidline placement of epidural catheters. We hypothesized that greater deviations of the epidural catheter insertion point from the ultrasound (US)‐determined midline would be associated with less effective labor analgesia. Methods: A prospective ethically approved cohort study was conducted. Fifty‐two healthy average‐sized women receiving labor epidural analgesia, inserted by the landmark technique, were approached after delivery. Immediately after removing the epidural catheter, we determined the epidural space midline using US and compared it to the epidural catheter insertion point and to the patient‐identified midline (assessed by a pinprick in 1‐mm increments). Correlations between the US midline‐to‐catheter insertion point distance and additional epidural local anesthetic requirements (primary outcome), pain verbal numeric rating scale scores (0–10) 1 hour after epidural insertion, and maternal satisfaction with analgesia were determined. The differences in distances were assessed by a Bland‐Altman analysis. Results: There were no significant correlations between the US midline‐to‐epidural catheter insertion point distance and additional epidural local anesthetic requirements ( R 2 = 0.138; P = .33), pain verbal numeric rating scale scores 1 hour after the epidural ( R 2 = 0.121; P = .40) or maternal satisfaction ( R 2 = 0.085; P = .57). The Bland‐Altman analysis revealed that the mean ± SD US midline‐to‐epidural catheter insertion point distance and patient‐identified midline distances were 0.38 ± 0.31 and 0.35 ± 0.46 cm, respectively. Conclusions: In our laboring population, the hypothesis that nonmidline epidural insertion is associated with less‐effective labor analgesia was not confirmed in this study cohort. We found minimal differences in distances between the US midline to epidural catheter insertion point and US midline to patient‐identified midline.